Comprehensive analysis of the physiological and molecular responses of phosphate-solubilizing bacterium Burkholderia gladioli DJB4–8 in promoting maize growth - Dao-Jun Guo; Dao-Jun Guo; Dao-Jun Guo; Guo-Rong Yang; Pratiksha Singh; Juan-Juan Wang; Juan-Juan Wang; Xue-Mei Lan; Rajesh Kumar Singh; Jing Guo; Yu-Die Dong; Dong-Ping Li; et al. (Frontiers in Plant Science)
Phosphorus (P) is one of the essential macroelements for the growth of maize. The deficiency of P in maize will result in adverse effects, including chlorosis and reduced yield. The Hexi Corridor in China serves as the principal region for seed maize production, with chemical phosphate fertilizer remaining the predominant source of P delivery for local maize cultivation. Nonetheless, the agricultural non-point source pollution resulting from the prolonged application of artificial phosphate fertilizers is intensifying. P in farmland soil often exists in an insoluble form, which plants cannot directly absorb and utilize. Phosphate-solubilizing bacteria (PSB) in the rhizosphere are a kind of plant growth-promoting rhizobacteria (PGPR) that can transform insoluble P in soil into soluble P for plants to absorb and utilize. Utilizing PGPR in agricultural production is an ecological approach to achieving sustainable development in agricultural practices and output. In this study, 41 strains of bacteria were isolated from the rhizosphere soil of four maize varieties. According to an in vitro plant growth-promoting (PGP) feature study and 16S RNA molecular identification, Burkholderia gladioli DJB4-8, among all strains tested, exhibited the highest in vitro PGP activity, with a phosphate-solubilizing ability of 8.99 mg/L. By scanning electron microscope (SEM) and green fluorescent protein (GFP) labeling technique, it was found that strain DJB4–8 formed a colonization symbiotic system with maize roots. The inoculation of maize Zhengdan 958 with strain DJB4–8 altered the plant’s photosynthetic physiology and indole-3-acetic acid (IAA) level, and it also dramatically increased the plant’s growth rate. The combined analysis of transcriptome and metabolomics showed that the key genes and metabolites in the interaction between strain DJB4–8 and maize were mainly concentrated in plant growth key pathways such as plant hormone signal transduction, phenylalanine, tyrosine and tryptophan biosynthesis, phenylalanine metabolism, phenylpropane biosynthesis, pentose phosphate pathway, zeatin biosynthesis, amino sugar and nucleotide sugar metabolism, and glutathione metabolism. These findings shed light on the need for additional research into the mechanism of interaction between PSB and maize.